Preventive measures against the COVID-19 pandemic in Mexico: A cross-sectional study - Ibarrola-Peña, Juan Carlos; Barbosa-Camacho, Francisco José; Almanza-Mena, Yolanda Lorelei; Chejfec-Ciociano, Jonathan Matías; Reyes-Elizalde, Emilio Alberto; Romero-Limón, Olaya Moramay; Zaragoza-Organista, Rafael; Cervantes-Pérez, Enrique; Sapién-Fernández, José Héctor; Guzmán-Barba, José Aldo; Flores-Becerril, Paola; Ochoa-Rodríguez, Itzel; et al. (Frontiers in Public Health, 2022)
Understanding how Mexicans behave during the pandemic could present a complete picture of the pandemic in Mexico while providing better handling of the pandemic. Objective: To analyze about the Mexican population's behavior and preventive measures. Methods: This was a cross- sectional study in which a total of 4004 participants from the general population responded to the survey. Results: Almost 99% of the participants mentioned knowing the symptoms of COVID-19. Although 77.5% of participants considered that they followed proper social distancing measures, 60% of them mentioned that they knew at least six individuals who did not follow social distancing measures. Furthermore, 96.2% of participants reported using preventive measures at least 50% of the time. Only 51.3% used a certified mask. Conclusion: The COVID-19 pandemic outcomes in Mexico are the result of multiple negative factors, such as high rates of comorbidities, a high number of people living together at home, many people breaking social isolation; and most of the population using noncertified preventive measures that may not be effective enough.